BOOK REVIEW: Radomir Popovic, "Serbian Orthodox Church in History" (translated in English by Petar V. Serovic, Belgrade and Novi Sad: Art Print, 2005), 135 p. - MORARIU, Maxim (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2016)
The history of the Serbian Orthodox Church is known in the Romanian space, but also in the other Orthodox spaces, mostly due to the activity of some important Serbian personalities, like Saint Nikolas Velimirovic or Saint Justin Popovic. The main reason for such a problem is the fact that most of the works dedicated to this subject are not translated in English or French. Therefore, the publication of some works like the one of Bosko Bojovic about the Serbian Orthodox Church means a lot for the research of this subject in other cultural spaces. However, if the aforementioned work is addressed to specialists, the one of Professor Radomir Popovic, who teaches History of the Church at the Faculty of Orthodox Theology in Belgrade, can be read and analysed by anyone who wants to improve his/her knowledge about this subject. It is similar to the synthesis about the history of our Orthodox Church, published by Father Mircea Păcurariu.